صناعة الخدمات المالية الإسلامية - تحديات الحاضر وآفاق المستقبل بعد 50 عامًا من الممارسة: Islamic Financial Services Industry - Present Challenges and Future Prospects After 50 Years of Practice - فضل عبد الكريم البشير, (Journal of North African Economies, 2025)
This research seeks to examine and critically analyze the major challenges confronting the Islamic financial services industry over the course of five decades of practice, while simultaneously offering proposals to mitigate these challenges. Employing a descriptive and analytical methodology, the study identifies and discusses a range of critical issues. These include the divergence of legal and regulatory frameworks governing Islamic banking across different jurisdictions; the difficulties encountered by Islamic banks in implementing the standards set forth by the Basel Committee; the inconsistencies in fatwas issued on identical jurisprudential matters; the persistent challenges associated with the development and innovation of Islamic financial products; and the limited scholarly engagement with academic research in this field. Furthermore, the study addresses the implications of broader economic and political transformations that continue to shape the trajectory of the industry. In response to these challenges, the research proposes a number of strategies and recommendations designed to strengthen the resilience and sustainability of the Islamic financial services sector. It also articulates a forward-looking vision for the industry, emphasizing the importance of aligning institutional practices with both regulatory requirements and the ethical foundations of Islamic finance. The study concludes with a call for greater academic rigor, underscoring the urgent need for graduate students and specialized researchers to undertake comprehensive and methodologically sound investigations into key thematic areas. Such contributions, it argues, are indispensable for advancing knowledge, informing policy, and ensuring the continued development and global relevance of the Islamic financial services industry. Keywords Islamic financial services industry. Challenge of developing Islamic financial products. Challenge of differing religious rulings. Challenge of implementing Basel international standards Challenge of weak interest in scientific research JEL CLASSIFICATION: E44.E58.E59: KAUJIE CLASSIFICATION: k1.J42.l25.Q23